Effect of counselling on psycho-social adjustment on elderly in Makurdi metropolis - Owunebe, Anna Ngweye (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
This paper examined the effect of counselling on psycho-social adjustment of aged people in Makurdi Metropolis. The study employed a quasi-experimental design based. The study sample 30 aged people. The instrument used for data collection was Aged People Psycho-Social Adjustment Questionnaire (CAPPSA). The data was analyzed using descriptive statistics of mean and standard deviation to answer the research questions. ANCOVA was used to test the hypotheses at .05 level of significance. The findings revealed that counselling has significant effect on adjustment to anxiety and self-acceptance among the aged people. It was recommended that government and Non-Government Organizations (NGOs) should work together in making provisions such as aged people home with counselling unit equipped with profession in order to support the aged to properly adjust to psychology disorders such as anxiety among others.